Structural, thermal and morphological characterization of UV-graft polymerization of acrylated-epoxidized soybean oil onto goat leather - Urena-Nunez, Fernando; Vigueras-Santiago, Enrique; Hernandez-Lopez, Susana; Linares-Hernandez, Karla; Linares-Hernandez, Isabel (Publishing House of Lviv Polytechnic National University, 2008)
Graft of acrylated-epoxidized soybean oil onto goat leather was achieved using UV-radiation. Graft percentage, structural, morphological and thermal characterizations are discussed in terms of: morphology of the leather grafted face and the UV-radiation dosage. The obtained results are of importance since an environmental friendly monomer could be used to change or improve some properties of leather articles. Проведено прищеплення акрилат-епоксидованої соєвої олії на козячу шкіру з використанням УФ-випромінювання. Встановлено відсоток прищеплення, морфологічні та термічні характеристики в залежності від морфології поверхні шкіри і дози випромінювання. Отримані результати вказують на безпечність використання такого мономеру для покращення властивостей шкіряних виробів.
Структурні, тематичні та морфологічні характеристики УФ-прищепленої полімеризації акрилат-епоксидованої соєвої олії на козячу шкіру
Keywords: leather; acrylated-epoxidized soybean oil; graft copolymer; UV-radiation; шкіра; акрилат-епоксидована соєва олія; прищеплений полімер